Connections, communities, and coinage - Watson, George Christopher. (New York, NY)
xix, 620 sayfa, [74] sayfa resim
Keywords: “This book sets out the system of shared dies and workshops of engravers that underlay production of the Roman provincial coinage in southern Asia Minor in the mid-third century AD and explores its implications both for the coinage and for the society of the region. The text is accompanied by a catalogue of coins“ --